The value of multimodal ultrasonography in evaluating therapeutic response of cervical tuberculous lymphadenitis to anti-tuberculosis drugs - Yu, Tianzhuo; Zhang, Lin; Xu, Jianping; Meng, Jun; Yu, Xiulei; Zhang, Ying (Frontiers in Medicine, 2023)
Purpose In order to research the value of multimodal ultrasonography in evaluating therapeutic response of cervical tuberculous lymphadenitis to anti-tuberculosis drugs. Materials and methods Sixty-one patients with cervical tuberculous lymphadenitis were enrolled in this study. Ultrasound examination was performed before systemic standard anti-tuberculosis treatment and within 1–2 months after treatment, and the patients were divided into effective group and ineffective group according to the follow-up at the sixth month. The multimodal ultrasound signs of the two groups were compared and analyzed. Results In the effective group, there were significant differences in the maximum diameter of lymph nodes, the echo of the surrounding tissue and the enlargement of the contrast area before and after treatment (p < 0.05). At 1–2 months after treatment, there were significant differences in the maximum diameter, pus changes, CDFI, elasticity scores, echo of surrounding tissues, changes in enlarged and non-enhanced areas after contrast enhancement between the effective group and the ineffective group (p < 0.05). Conclusion The multimodal ultrasound signs of the appearance of internal pus or non-enhancement area enlargement, enhanced echo of the surrounding tissue and enlargement after CEUS are related to poor prognosis, and may be used to evaluate the response of anti-tuberculosis chemotherapy when the size change of lymph node is not obvious in individual treatment.